2021
DOI: 10.1186/s13568-021-01333-2
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule targeting amyloid fibrils inhibits Streptococcus mutans biofilm formation

Abstract: Amyloid fibrils are important scaffold in bacterial biofilms. Streptococcus mutans is an established cariogenic bacteria dwelling within biofilms, and C123 segment of P1 protein is known to form amyloid fibrils in S. mutans biofilms, among which C3 segment could serve as a promising anti-amyloid target due to its critical role in C123-P1 interactions. Recently, small molecules have been found to successfully inhibit biofilms by targeting amyloid fibrils. Thus, our study aimed to screen small molecules targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
5
1
Order By: Relevance
“…Second, once nonamyloid-related background reactivity stemming from the presence of cell wall material was eliminated by filtration of biofilm samples, ThT fluorescence assays also identified amyloid material only in the nonadherent fraction of the older biofilm. Although other studies have reported, based on ThT uptake alone, that amyloid formation is an early event associated with adherent S. mutans biofilms ( 53 55 ), our more rigidly controlled experiments indicate otherwise. The third line of evidence comes from confocal microscopy and immunostaining with two different C123-reactive monoclonal antibodies that can discriminate between amyloid and nonamyloid forms of the polypeptide.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Second, once nonamyloid-related background reactivity stemming from the presence of cell wall material was eliminated by filtration of biofilm samples, ThT fluorescence assays also identified amyloid material only in the nonadherent fraction of the older biofilm. Although other studies have reported, based on ThT uptake alone, that amyloid formation is an early event associated with adherent S. mutans biofilms ( 53 55 ), our more rigidly controlled experiments indicate otherwise. The third line of evidence comes from confocal microscopy and immunostaining with two different C123-reactive monoclonal antibodies that can discriminate between amyloid and nonamyloid forms of the polypeptide.…”
Section: Discussioncontrasting
confidence: 86%
“…While some studies have utilized in situ uptake and fluorescence intensity of the amyloidophilic dye ThT as a direct indicator of the presence of amyloid within growing S. mutans biofilms ( 53 55 ), ThT fluorescence can be misleading due to an interaction of ThT with nonamyloid components of the biofilms. Although amyloid formation is a biofilm-associated process for S. mutans ( 27 , 28 ), we have shown previously that planktonically grown wild-type S. mutans , as well as mutants lacking P1, WapA, and Smu_63c, or Sortase A, all demonstrate an identical uptake of ThT ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besingi et al screened and identified a benzoquinone derivative AA-861, which exhibited antibiofilm effects against S. mutans by targeting amyloid fibrils, an important scaffold in S. mutans biofilms (Besingi et al, 2017). Chen et al also screened and identified a small molecule, namely D25, which targeted amyloid fibrils and selectively inhibited S. mutans biofilms (Chen et al, 2021).…”
Section: Streptococcus Mutansmentioning
confidence: 99%
“…Chen et al. also screened and identified a small molecule, namely D25, which targeted amyloid fibrils and selectively inhibited S. mutans biofilms ( Chen et al., 2021 ).…”
Section: Small Molecules That Inhibit Keystone Bacteria Associated Wi...mentioning
confidence: 99%
“…The interactions between C123 (C-terminal segment) and P1 contribute to biofilm-related events such as amyloid fibrils formation, suggesting that C3 would serve as a promising anti-amyloid target ( Rivière et al., 2020 ). Chen ( Chen et al., 2021 ) selected small molecules targeting C3 through structure-based virtual screening, and found that D25 selectively inhibited amyloid fibrils and S. mutans biofilms but had little influence on biofilms formed by S. gordonii and S. sanguinis .…”
Section: Computer-aided Drug Design (Cadd)mentioning
confidence: 99%